The presence of arsenic in minerary activities: a scientometric analysis (Research, Society and Development, 2019)
Mining is an important activity for the economic development of a country, besides being essential for the improvement of the quality of life and social welfare. However, this sector may trigger negative environmental and health impacts associated with trace element contamination, such as arsenic (As). Thus, this article aimed to evaluate the spatio-temporal evolution of published and indexed scientific papers, from 1982 to 2017, in the Web of Science database related to the presence of this element in mining activities. A qualitative and quantitative documentary research was carried out using the scientometry method, which resulted in a sample of 833 articles. The results obtained point to the evolution of the number of articles published during the period analyzed, with the countries with the largest number of publications being the Netherlands (27.7% of the citations), the United States (25.1%) and England (17.5%). It was possible to note that the most used analysis techniques of As were the atomic fluorescence spectrometry, atomic absorption spectrometry and X-ray diffraction spectrometry mentioned in 54.9% of the articles. In addition, the most applied removal techniques in contaminated environments correspond to phytoremediation with 43.1% of citations and bioremediation with 19%. It should be noted that research involving contamination triggered by anthropic activities is an important knowledge instrument for detection, prevention and / or mitigation of impacts caused by contamination by trace elements.